An assessment framework for measuring agroecosystem health. (August 2017) - Peterson, Erin E.; Cunningham, Saul A.; Thomas, Mark; Collings, Simon; Bonnett, Graham D.; Harch, Bronwyn
Highlights: Pressure is increasing for agricultural industries to report on sustainability. Industries currently report on agroecosystem health (AEH) using disparate methods. We present a formal AEH assessment framework that is flexible and adaptive. The framework includes diagnostic indicators explicitly linked to management. It can be tailored to local issues and used to compare across regions or industries. Abstract: There are inherent social, environmental, and economic trade-offs in agricultural systems, which by definition have been altered from their natural state by humans for food and fibre production. Consumers are increasingly concerned about the environmental and social impacts of agriculture, and with the increasing influence of social media, agribusinesses and industries can be held accountable for their actions in the public domain. Thus, environmental sustainability reporting is increasingly being viewed as a cost of doing business in agriculture. There are a number of approaches used to measure agroecosystem health (AEH) around the world, but they are generally designed to make comparisons at coarse spatial scales (i.e. nations) or report on specific management actions implemented at the local scale (i.e. farm, catchment, or sub-region). Here we present a simple, yet scientifically robust assessment framework that can be used to benchmark and monitor the specific impacts of agricultural management practices on the environment. The general principles are drawn from environmental monitoring and experiences gained in environmental assessments that are not necessarily agriculturally focussed. However, many commonly used environmental indicators are not suitable for AEH assessment because they do not explicitly link environmental outcomes to management actions; or they fail to separate specific agricultural impacts from broader cumulative impacts resulting from other industries or land uses. We recommend using a combination of diagnostic, outcome-based indicators, in addition to practice- and product-based measures to communicate efforts to improve agroecosystem health outcomes. The framework presented here enables assessments at local scales, but can be aggregated or disaggregated to report at finer or coarser scales. This flexibility ensures that the assessment is relevant to the proponent and stakeholders, while also providing a way to make comparisons between producers, industries, or regions as part of an adaptive monitoring and assessment framework. This also opens the door for industry-based AEH monitoring program to provide, or make use of information from government-funded environmental monitoring programs, with benefits to both.